DIFFERENT CRITERIA BETWEEN DERIVATIONAL AND INFLECTIONAL MORPHEMES IN ENGLISH - Adi Yusuf (Universitas Nahdatul Ulama Surabaya, 2017)
In learning English words, it is very important to know the smallest unit which contributes to determine a new word or meaning, called ‘morpheme’. There are two kinds of morphemes whether they create a new word or a new meaning: derivational morphemes and inflectional morphemes. This paper would like to discuss some different criteria that help to distinguish between English inflectional and derivational affixes, they are: (a) derivational affixes change a word and/or the meaning, but not all. However, inflectional affixes do not., (b) the place of derivational affixes is closer than that of inflectional affixes, the place of inflectional affixes is outside derivational affixes., (c) derivational affixes apply to restricted classes of stems, while inflectional affixes barely have exception., (d) derivational affixes are not relevant to the syntax, however inflectional affixes are relevant., (e) derivational morphemes can be attached by prefixes and suffixes, on the other hand, inflectional morphemes are only added by suffixes., and (f) derivational morphemes are semantically opaque, while inflectional morphemes are rarely semantically opaque.